2021
DOI: 10.1161/strokeaha.120.032139
|View full text |Cite
|
Sign up to set email alerts
|

Centrum Semiovale Perivascular Space and Amyloid Deposition in Spontaneous Intracerebral Hemorrhage

Abstract: Background and Purpose: We explored whether high-degree magnetic resonance imaging–visible perivascular spaces in centrum semiovale (CSO) are more prevalent in cerebral amyloid angiopathy (CAA) than hypertensive small vessel disease and their relationship to brain amyloid retention in patients with primary intracerebral hemorrhage (ICH). Methods: One hundred and eight spontaneous ICH patients who underwent magnetic resonance imaging and Pittsburgh compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…[ 9 , 33 , 37 ] Δ The early-phase 11c-PiB PET help differentiate probable CAA from probable AD. Early-phase amyloid PET images are used as a surrogate for brain perfusion, as opposed to the standard late-phase 11c-PiB PET/CT which reflects binding to aβ deposits ◊ When predominantly placed in the centrum semiovale, the dilated perivascular spaces are frequently associated with CAA [ 72 ] § Microbleeds are not specific for CAA as they can be seen in multiple conditions, including, hypertension, cerebral cavernous malformations, coagulopathy, thrombocytopenia, anticoagulant medications, CNS vasculitis, infective endocarditis, end-stage kidney failure. Moreover, beside conditions above-mentioned, microbleeds are also more prevalent among users of antiplatelet agents [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 , 33 , 37 ] Δ The early-phase 11c-PiB PET help differentiate probable CAA from probable AD. Early-phase amyloid PET images are used as a surrogate for brain perfusion, as opposed to the standard late-phase 11c-PiB PET/CT which reflects binding to aβ deposits ◊ When predominantly placed in the centrum semiovale, the dilated perivascular spaces are frequently associated with CAA [ 72 ] § Microbleeds are not specific for CAA as they can be seen in multiple conditions, including, hypertension, cerebral cavernous malformations, coagulopathy, thrombocytopenia, anticoagulant medications, CNS vasculitis, infective endocarditis, end-stage kidney failure. Moreover, beside conditions above-mentioned, microbleeds are also more prevalent among users of antiplatelet agents [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…◊ When predominantly placed in the centrum semiovale, the dilated perivascular spaces are frequently associated with CAA [ 72 ]…”
Section: Resultsmentioning
confidence: 99%
“…We also excluded patients with CAA-related ICH to avoid the potential confounding effect of the different topographical distribution of damaged vessels in β-amyloid disorders. 16 Further study focusing on CVR in CAA to delineate the complex relationships between β-amyloid deposition, venous flow alterations and SVD injuries to the brain should be done. Finally, the sample size in this study was relatively small and our cross-sectional design could not assess the causality between CVR and PVS enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of PET imaging with 11 C-PIB for the differential diagnosis between CAA and other conditions related to cerebral hemorrhage has been proven in some studies [18,28,32,37,42].…”
Section: Role Of Pet Imaging For the Assessment Of Caamentioning
confidence: 99%
“…In this setting Ly et al [18] reported increased 11 C-PIB uptake in patients with CAA-related hemorrhage (CAAH) and higher binding of tracer in patients with probable CAAH compared to patients with possible CAAH. Four different studies by the group of Tsai et al [28,32,37,42] reported higher 11 C-PIB retention in CAA-ICH patients compared to non-CAA-ICH patients (hypertensive and mixed ICH) and a correlation between lobar lacune counts and SUV values. Furthermore, higher tracer uptake in patients with high-degree enlarged centrum semiovale perivascular spaces (ECSPVS) compared to low-degree patients was reported.…”
Section: Correlation With Cmb and Differential Diagnosis Of Ichmentioning
confidence: 99%